Disease of Mikania micrantha kunth - Rahiman, bin Jumat (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study was done to identify fungi associated with diseases of perennial weed, Mikania micrantha Kunth. Samples were collected from two places, Petra Jaya and Kota Semarahan. The common disease on M. micrantha was leaf spots. The disease symptoms were shown by the present of yellowish brown spots. Pathogens were isolated from spots of the infected leaves using media potato dectrose agar (PDA). After incubated at room temperature, various types of fungi were found . A total, 16 species of fungi were isolated from the leaf diseases of M. micrantha. Morphological structures of the fungi were used for identification. The fungi that had been identified were including Phomopsis sp., Colletotrichum sp., Fusarium sp. and Trichoderma sp .. Pathogenicity tests of the selected fungi were done by inoculating the mycelium of the fungi on detached leaves of M. micrantha. All of the tested fungi were able to produce disease symptoms. Observations on effect of temperature on growth of the fungi were also done. Most of the fungi grew significantly faster at P=O.05 at temperature 25°C to-30°C.